Dose Analysis of In Vitro and In Vivo Test for Boron Neutron Capture Therapy (BNCT) - Hamidatul Faqqiyyah; Sunarno Sunarno; Isa Akhlis; Yohannes Sardjono (Universitas Gadjah Mada, 2018)
The purpose of this study was to determine the in vitro and in vivo doses of boron neutron capture cancer therapy (BNCT) using the SHIELD-HIT12A program. To be able to determine the recoil energy, the research was conducted using the Monte Carlo method. Running data obtained the value of ionization activity and recoil lost. The results showed that in vitro and in vivo doses of BNCT for soft tissue irradiation had a value of 0.312 × 10-2 Sv, which is safe and does not harm healthy body tissue around the cancer cells because it is below the threshold of 1.5 Rem or 15 × 10-3 Sv, in accordance with the provisions of the upper value permitted by the International Commission on Radiation Protection in 1966. While the comparative targets are water, the optimal target absorption dose was obtained at concentrations of 3.232 × 10-3 Gy. The dose of carbon equivalent in water with the type of thermal neutron radiation was 16.16 × 10-3 Sv; this dose is classified as unsafe.